Effect of calcium chloride treatment by vacuum infiltration method on texture and shelf life of black cherry tomatoes (Solanum lycopersicum cv. OG) - Ngan, Ha Ho Thi; Thanh, Qui Tran; Nguyen, Tri Tin; Nguyen, Thanh Thu; Nguyen, Trong Son; Huyen, Trang Duong Ti; Nguyen, Minh Thuy (Penerbit Universiti Kebangsaan Malaysia, 2020)
The use of vacuum infiltration in the food industry has several advantages, such as improving the quality, eliminating chemical treatment requirements, stabilizing products, and retaining nutrients during storage and processing. This study was performed to optimize the vacuum level (516-684 mmHg), treatment time (10-20 min), and calcium chloride (CaCl2) concentration (0.58- 1.42%) using the Response Surface Methodology (RSM). The firmness of black cherry tomatoes (Solanum lycopersicum cv. OG) reached an optimum value (1477.81 g/cm2) when fruits were treated at a vacuum level of 637 mmHg with a concentration of CaCl2 1.09% for 17 min. Meanwhile, the firmness was 746 g/cm2 for the control sample, which was dipped in 1.42% CaCl2 solution for 20 min at the atmospheric condition. The scanning electron microscope (SEM) images of stomata of two samples with/without vacuum treatment were also significantly different. The sample after vacuum treatment at optimum parameters was put into PE and PP bags for storage at 10-12°C. Vacuum-infiltrated tomatoes contained in PE and PP bags had a corresponding storage time of 30 and 28 days. The control samples were maintained for shorter periods, only 22 and 20 days, respectively.